Association between dietary approaches to stop hypertension eating pattern and lung cancer risk in 98,459 participants: results from a large prospective study - Zhu, Zhiyong; Peng, Linglong; Gu, Haitao; Tang, Yunhao; Xiao, Yi; He, Hongmei; Yang, Mingying; Xiang, Ling; Wang, Yaxu (Frontiers in Nutrition, 2023)
Background Dietary approaches to stop hypertension (DASH) eating pattern is linked to anti-inflammatory responses and antioxidation, which overlap with the pathogenesis of lung cancer. However, there is insufficient epidemiological evidence to link this dietary pattern to lung cancer risk conclusively. Aim To determine if adherence to the DASH diet is linked to a lower risk of developing lung cancer in a large prospective study. Methodology The data of participants were retrieved from the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial. A DASH score was calculated based on 8 dietary components to reflect adherence to DASH, with greater scores representing higher adherence. Three Cox proportional hazards models were constructed to analyze the association between DASH scores and lung cancer risk, including an unadjusted model and two adjusted models (model 1 for demographics and model 2 for fully confounding factors). A restricted cubic spline plot was utilized to illustrate the likelihood of developing lung cancer across the entire range of DASH scores. The association between each of the 8 DASH components and the risk of lung cancer was assessed separately. Several subgroup analyses were conducted to identify potential modifiers, and several sensitivity analyses were performed to verify the robustness of the findings. Results The study involved 98,459 individuals in total. The mean (standard deviation) DASH score was 24.00 (4.62) points, along with the mean follow-up period of 8.84 (1.94) years. Lung cancer was identified in 1642 cases over 869807.9 person-years of follow-up, and the overall incidence rate was 0.189 cases/100 person-years. Participants in the highest quartile in the fully adjusted model had a relatively decreased risk of developing lung cancer in comparison to those in the lowest quartile (HRquartile 4 versus 1: 0.647; 95% CI: 0.557, 0.752; Ptrend < 0.001). The restricted cubic spline plot demonstrated that DASH score and lung cancer risk were inversely associated and had a linear dose–response relationship (Pnon-linear = 0.944). According to subgroup analyses, those who were current or former smokers had a stronger inverse connection than those who never smoked (Pinteraction = 0.013). The results remained robust after several sensitivity analyses. Conclusion The risk of lung cancer was inversely associated with DASH scores in the US population. This suggests that following the DASH pattern can help prevent lung cancer, especially for current or former smokers. More epidemiological evidence from other regions and populations is needed to confirm our findings.